Hubungan Pemberian ASI Ekslusif terhadap Perkembangan Kognitif Anak Usia 18-24 Bulan di Posyandu Bougenvile Desa Ngandong Kecamatan Grabangan Kabupaten Tuban - Siti Marliana; Malikatus Sholihah; Dwi Aminatus Sa’adah (Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Early childhood education is the level where early childhood enters the first stage before going to elementary school. Early childhood education has 6 aspects of development that must be developed, namely the development of religious and moral values, physical-motor development, social-emotional development, artistic development, language development, and cognitive development. This study aims to describe whether there is a relationship between exclusive breastfeeding on the development of children aged 18-24 months, and to describe the relationship between exclusive breastfeeding on children's cognitive development. This research is a qualitative descriptive study with a sample of 20 informants. Data collection methods used are group discussion forums, observations, interviews, and documentation. The research data obtained were then analyzed using thematic analysis. The results showed that there was a relationship between exclusive breastfeeding on child development, and exclusive breastfeeding on the cognitive development of children aged 18-24 months at Posyandu Bougenvile, Ngandong Village, Grabangan District, Tuban Regency.